2020
DOI: 10.1002/jnr.24674
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal neuroimaging in anorexia nervosa

Abstract: Anorexia nervosa (AN) is a severe and complex psychiatric disorder characterized by intense fear about weight gain and finalized to food-related control behaviors. Growing interest has been demonstrated about neurobiological processes subtend to AN physiopathology. The present review aimed to collect neurostructural and neurofunctional available data from 2010 to 2019. Results have been organized according to the neuroimaging technique employed, also including a specific section on electroencephalographic resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 138 publications
(199 reference statements)
0
6
0
Order By: Relevance
“…Some of the abnormalities reported in acute AN tend to reverse after remission of symptoms, in particular alterations in white matter microstructures [ 108 ]. Studies on patients with BN and BED reported primarily alterations in circuits involved in appetite, the processing of food stimuli, and impulse control rather than in circuits involved in the understanding of others’ mental states [ 109 ], while structural and functional abnormalities are generally less extensive and pervasive in patients with BN or BED than in those with AN.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the abnormalities reported in acute AN tend to reverse after remission of symptoms, in particular alterations in white matter microstructures [ 108 ]. Studies on patients with BN and BED reported primarily alterations in circuits involved in appetite, the processing of food stimuli, and impulse control rather than in circuits involved in the understanding of others’ mental states [ 109 ], while structural and functional abnormalities are generally less extensive and pervasive in patients with BN or BED than in those with AN.…”
Section: Discussionmentioning
confidence: 99%
“…These functional alterations are in line with data emerging from electroencephalography studies, showing decreased electrical activity in frontal and parietal-occipital regions during cognitive tasks. Likewise, altered electrical activity in fusiform gyrus and parahippocampal gyrus is demonstrated during resting-state paradigms [25].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding eating disorders such as AN and also Bulimia nervosa (BN), the processing of disorder-relevant stimuli in terms of for example, food stimuli or body pictures was investigated, pointing to an impaired stimuli processing compared to healthy controls (HCs) (Alfano et al, 2020;Mai et al, 2015;Wolz et al, 2015): Novosel et al (2014) investigated the processing of food stimuli in 11 adolescents with AN in comparison to age-matched HCs: they reported a higher LPP in patients with AN while watching stimuli passively, pointing to a stronger AB towards food pictures compared to HCs. Furthermore, within the AN group, a greater AB was found for low calorie, but not high calorie pictures compared to HCs (Novosel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the pathophysiology and the underlying mechanisms of AN, the investigation of the neurobiological, ‐structural or ‐physiological correlates of altered stimuli‐processing is mandatory. While neurostructural and neurofunctional studies of AN often use MRI or fMRI (Kappou et al., 2021; Su et al., 2021), the application of non‐invasive electroencephalography (EEG) and analyses of event‐related potentials (ERPs) are less prevalent in this population (Alfano et al., 2020; Wolz et al., 2015). Especially, due to the high temporal resolution of EEG, it is a very useful and complementary methodology to assess stimuli‐specific neuronal processing.…”
Section: Introductionmentioning
confidence: 99%